1981
DOI: 10.1175/1520-0477(1981)062<0031:saorro>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Recent Research on the Qinghai-Xizang Plateau Meteorology

Abstract: The Qinghai-Xizang (Tibet) Plateau has a profound influence on atmospheric circulation patterns on all time and space scales. This report constitutes a short summary of work being performed at the Lanzhou Institute of Plateau Atmospheric Physics of the Academia Sinica. A short discussion of the climatic characteristics of the plateau is followed by a description of the main features of annual and diurnal cycles in pressure and circulation patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 0 publications
0
46
0
Order By: Relevance
“…The importance of the Tibetan Plateau as a heat source for the summer monsoon has been discussed by many authors (Gao et al, 1981;Fu and Fletcher, 1985;Luo and Yanai, 1984;Murakami, 1987Murakami, , 1993. Li and Yanai (1996) suggested that the onset of the low-level monsoon southwesterlies, which occur on the south side of the Tibetan Plateau, are concurrent with the reversal of the meridional temperature gradient south of the Tibetan Plateau.…”
Section: Temperature Fields Over the Tibetan Plateaumentioning
confidence: 99%
“…The importance of the Tibetan Plateau as a heat source for the summer monsoon has been discussed by many authors (Gao et al, 1981;Fu and Fletcher, 1985;Luo and Yanai, 1984;Murakami, 1987Murakami, , 1993. Li and Yanai (1996) suggested that the onset of the low-level monsoon southwesterlies, which occur on the south side of the Tibetan Plateau, are concurrent with the reversal of the meridional temperature gradient south of the Tibetan Plateau.…”
Section: Temperature Fields Over the Tibetan Plateaumentioning
confidence: 99%
“…In this region, the intensity of disturbances, the frequency of occurrence of synoptic-and mesoscale systems, and the instability of the atmosphere are unique when compared with other regions of the same latitude and elevation (Gao et al, 1981). The boundary layer of the Plateau has the most frequent synoptic-scale and mesoscale pressure systems of all regions in the same latitude belt and of similar elevation.…”
Section: Resultsmentioning
confidence: 98%
“…The strong and active convectional activity is very important for the maintenance of the large-scale circulation system on the Plateau (Yang et al, 1990). During the summer half of the year, on average, a small high, or a low-pressure vortex and a shear line, forms every two days over the Plateau (Gao et al, 1981). The large-scale convergence environment usually forms in the afternoon in the monsoon season, which provides a favourable condition for the generation of local convection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tibet is one of the most intensive solar radiation regions in the world [11]. Its annual total amount of radiation at Mount Qomolangma (Everest) is 8332 MJ m , only a little less than that in Poona (8583 MJ m ), India, and Cairo (8374 MJ m ), Egypt [6]. Due to the high elevations of the Tibetan Plateau, the air mass over it is only half of that over the adjacent low-level terrain.…”
mentioning
confidence: 99%